2022
DOI: 10.3389/fpls.2021.821954
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on Degraded Alpine Grassland Mediated by Climate Factors: Enlightenment for Ecological Restoration

Abstract: Alpine grassland is the main ecosystem on the Qinghai-Tibet Plateau (QTP). Degradation and restoration of alpine grassland are related to ecosystem function and production, livelihood, and wellbeing of local people. Although a large number of studies research degraded alpine grassland, there are debates about degradation patterns of alpine grassland in different areas and widely applicable ecological restoration schemes due to the huge area of the QTP. In this study, we used the meta-analysis method to synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…These results indicated that the discrepancy of groundwater depth in specific terrains may form a specific microclimate or habitat traits that regulate vegetation growth and comprise a specific microenvironment, with the addition of desorption, dissolution, or the lateral export of groundwater, ultimately acting on the accumulation and distribution of nutrients in different profiles of soils ( Shi and Shao, 2000 ; Wang, 2002 ; Xu et al., 2012 ; Yu et al., 2019 ). Several studies suggested that precipitation was the driving factor of nutrient distribution in soil profiles at global, regional, and site scales ( Zhang et al., 2019 ; Yu et al., 2022 ). However, in arid and semi-arid regions characterized by scarce rainfall and intense evaporation, groundwater serves as a vital and sole source of water, and the variability of soil moisture primarily depends on groundwater depth.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the discrepancy of groundwater depth in specific terrains may form a specific microclimate or habitat traits that regulate vegetation growth and comprise a specific microenvironment, with the addition of desorption, dissolution, or the lateral export of groundwater, ultimately acting on the accumulation and distribution of nutrients in different profiles of soils ( Shi and Shao, 2000 ; Wang, 2002 ; Xu et al., 2012 ; Yu et al., 2019 ). Several studies suggested that precipitation was the driving factor of nutrient distribution in soil profiles at global, regional, and site scales ( Zhang et al., 2019 ; Yu et al., 2022 ). However, in arid and semi-arid regions characterized by scarce rainfall and intense evaporation, groundwater serves as a vital and sole source of water, and the variability of soil moisture primarily depends on groundwater depth.…”
Section: Discussionmentioning
confidence: 99%
“…We used random forest mean predictor IncNodePurity (increase in node purity) to characterize the main predictors (Wang et al., 2021). We used the meta‐regression models to determine the relationship between RR of biomass and C:N:P ratio with warming magnitude and climate factors (van Houwelingen et al., 2002; Yu et al., 2022). Here, only results with more than three comparisons are displayed (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, approximately 70% of alpine grassland has been degraded in recent decades ( Peng et al., 2019 ). The degradation of grasslands has resulted in soil erosion ( Liu et al., 2018 ; Li et al., 2019 ; Dai et al., 2021 ; Li et al., 2023 ) and biodiversity loss ( Wang et al., 2009 ; Yu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%